STUDI JUST IN TIME UNTUK MENINGKATKAN KINERJA PRODUKTIVITAS PERUSAHAAN - Ratna Kusumawati (Universitas Wahid Hasyim, 2009)
The research was held by literature study of the last risets about Just In Time system for company productivity performance. On this riset, was developed a model with four hypothesis, based on four major construct : supplier, velocity of production process, production system, productivity performance. The result were giving many causality as stated as on the hypothesis. Key words : Supplier, velocity of production process, production system, productivity performance